The role of 3D fields on runaway electron mitigation in ASDEX Upgrade: a numerical test particle approach. (28th May 2021) - Gobbin, M.; Marrelli, L.; Valisa, M.; Li, L.; Liu, Y.Q.; Papp, G.; Pautasso, G.; McCarthy, P.J.; Upgrade Team, the ASDEX; MST1 Team, the EUROfusion
Abstract: The data collected during ASDEX Upgrade experiments in which external 3D fields have been deployed in the attempt of mitigating runaway electrons (RE) are interpreted by a numerical test particle approach. To this end the Hamiltonian guiding center code ORBIT has been used, with the implementation of the magnetic perturbation spectrum modeled by the code MARS-F, which also takes into account the plasma response to the applied 3D fields. In agreement with the observed phenomenology, ORBIT simulations show that the configuration of the currents in the top/bottom arrays of error field coils, which maximizes the plasma response to the external perturbations, is the one that most affects the high energy test electron trajectories in the edge region, thus leading to an enhancement of the energetic electron losses. This occurs in particular during the disruption, i.e. taking into account the increased toroidal electric field associated with the fast plasma cooling. Used in a predictive way, the numerical results suggest which coil configuration could further improve the RE mitigation.